2015
DOI: 10.2139/ssrn.2682691
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Ambiguity and Political Representation

Abstract: We introduce a Downsian model in which policy-relevant information is revealed to the elected politician after the election. The electorate benefits from giving the elected politician discretion to adapt policies to his information. But limits on discretion are desirable when politicians do not share the electorate's policy preferences. Optimal political representation generally consists of a mixture of the delegate (no discretion) and trustee (full discretion) models. Ambiguous electoral platforms are essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…16 In our experiment, messages coded as "campaign promises" are arguably more precise about future intended behavior than other messages. Previous research has found that while precise messages can be viewed as signals of competence (Frenkel 2014), ambiguity is common and often not punished by voters (Kartik, Van Weelden, and Wolton 2017;Tomz and Van Houweling 2009). We find that higher-quality challengers send more precise messages (Table 8), consistent with Frenkel.…”
Section: Figure 5 Percent Of Messages In Close Elections and Landslidessupporting
confidence: 86%
“…16 In our experiment, messages coded as "campaign promises" are arguably more precise about future intended behavior than other messages. Previous research has found that while precise messages can be viewed as signals of competence (Frenkel 2014), ambiguity is common and often not punished by voters (Kartik, Van Weelden, and Wolton 2017;Tomz and Van Houweling 2009). We find that higher-quality challengers send more precise messages (Table 8), consistent with Frenkel.…”
Section: Figure 5 Percent Of Messages In Close Elections and Landslidessupporting
confidence: 86%
“…C H A P T E R 8 1. Kartik, van Weelden, and Wolton (2017) suggest that the relationship between position blurring and electoral outcomes is correlational, not causal: political parties (or candidates) that lead in electoral competition both blur their positions and win elections.…”
Section: The Future Of Position Blurring In Western Europementioning
confidence: 99%